Training on Virgin Coconut Oil (VCO) Making from Coconut Fruit in Batang Anai District, Padang Pariaman Regency - Trisna Kumala Sari (Pelita Eksakta, 2021)
Kataping, Batang Anai District, Padang Pariaman Regency is a suitable area for growing coconut. Coconut fruit has been used mostly for ingredients cook. Whereas this coconut fruit can be made the Virgin Coconut Oil (VCO) which is beneficial for health and also has antiviral properties. Therefore, the people of Ketaping, Batang Anai District, Padang Pariaman Regency need to be equipped with knowledge and skill to process the coconut fruit into Virgin Coconut Oil (VCO) which is used as an antiviral functional food product that can be consumed by families by attending a training. The activity carried out was the delivery of material by the resource person then continued with the direct practice of making Virgin Coconut Oil (VCO). This activity has a positive impact which can increase public knowledge about VCO, its benefits, and how to make it.